Key Thinkers on Space and Place - Gilmartin, Mary; Hubbard, Phil; Kitchin, Rob; Roberts, Sue (SAGE Publications, Ltd. (UK), 2024)
Space and place are at the heart of how geographers and sociologists think.  This updated edition of the essential undergraduate text will introduce you to the most influential thinkers in the tradition of social theory, with a new focus on the past fifty years.  This book is designed to engage with theoretical debates in human geography through the individuals who have made the most significant contributions to this field.  This will show you how ideas are shaped by contexts, and how those ideas in turn effect change. This book shows how theoretical understandings evolve, shift and change. It also highlights the connections between different thinkers, whose ideas are developed in collaboration with or in reaction to others. Spatial thought is never developed in a vacuum, but is always constructed by individuals and groups of people located in particular institutional and social structures, with their own sets of personal and political beliefs. The biographical approach of this book reveals how individual thinkers draw on a rich legacy of ideas from past and contemporary generations. With increased coverage of international and female thinkers, as well as those who work against Eurocentric notions of space and place, this book reveals the exciting reorientation of Geography towards new ideas and methods in the last decade.  Each entry contextualises its subject within on-going (inter)disciplinary debates and important political moments, as well as highlighting connections between different thinkers. Together the chapters uncover the rich and diverse evolution of social theory, equipping you with the foundational ideas of geographical thought.  Each entry offers the following components: i) a short biography ii) an explanation of ideas iii) an exploration of how their ideas have been used and critiqued iv) a selective bibliography of key publications (and key publications which review or critique)